A framework for targeting household energy savings through habitual behavioural change. Issue 7 (8th August 2016) - Pothitou, Mary; Kolios, Athanasios J.; Varga, Liz; Gu, Sai
Abstract : This paper reviews existing up-to-date literature related to individual household energy consumption. The how and why individual behaviour affects energy use are discussed, together with the principles and perspectives which have so far been considered in order to explain the habitual consuming behaviour. The research gaps, which are revealed from previous studies in terms of the limitations or assumptions on the methodology to alter individuals' energy usage, give insights for a conceptual framework to define a comprehensive approach. The proposed framework suggests that the individual energy perception gaps are affected by psychological, habitual, structural and cultural variables in a wider-contextual, meso-societal and micro-individual spectrum. All these factors need to be considered in order for a variety of combined intervention methods, which are discussed and recommended, to introduce a more effective shift in the conventional energy-consuming behaviour, advancing insights for successful energy policies.